Radioactivity in Farm Soils and Food Crops Grown in Jos and Abeokuta, Nigeria and its Associated Cancer Risks (2012)
Ionizing radiations resulting from either natural or artificial radioactivity are useful but associated with them are health risks which increase with exposure. The natural radioactivity levels in soils of some locations in Jos and Abeokuta are significantly higher than the world average. Enhanced internal and external radiation exposures to man may result from physical presence in, and ingestion of food items grown in these areas. Scientific data are sparse on the radionuclide contents in food crops, farm soils and their radiological implications on the population. Therefore the aim of this study was to determine the radioactivity levels of 40K, 226Ra and 232Th in food crops and farm soils, and associated cancer risks in the population in the areas. A total of 243 food crop samples from 19 commonly grown types including acha, cowpea, cassava, cocoyam, Guinea corn, maize and yam; and 106 soils samples were randomly collected from 40 farm lands, 23 in Jos and 17 in Abeokuta, selected at random. The samples were air dried to constant mass, pulverized, sieved to pass 2mm mesh-size and sealed for 4 weeks to attain secular equilibrium. The activity concentration of the radionuclides were determined by counting each sample for 10 hours using a gamma-ray spectrometer comprising 76mm x 76mm NaI(TI) detector coupled to a multichannel analyzer. The effective dose rates due to ingestion of the food crops and outdoor effective dose rates due to farm soils were evaluated using the calculated activity concentrations and food consumption rates from Federal Office of Statistics, Nigeria. The risk of incurring cancer from radiation exposure were evaluated using carcinogenicity radionuclide slope factors by United States Environmental Protection Agency and the linear non-threshold radiation risk model, and compared with the International Commission on Radiological Protection (ICRP) recommended limits. Data were analyzed using descriptive statistics. The concentration of 40K, 226Ra and 232Th in food crops in Jos ranged from 8.7-1406.1, 2.1-85.5 and 2.6-89.8 Bqkg-1 respectively; whereas in Abeokuta the range was 38.2-1648.3, 2.1-81.1 and 2.6-48.3 Bqkg-1 respectively. The concentration of 40K, 226Ra and 232Th in farm soils were respectively 698.0±416.0; 143.1±80.8 and 287.3±306.3 in Jos and 411.0±341.0; 65.0±29.0 and 184.0±205.0Bqkg-1 in Abeokuta. The radioactivity levels were higher in Jos than Abeokuta. The tin mining in Jos might be the principal differential factor for its elevated radioactivity compared to Abeokuta. The annual average effective doses due to food ingestion in Jos was 0.20.01Sv (cowpea), 1852.0±43.1μSv (yam); in Abeokuta 58.7±15.7μSv (cocoyam) and 1064.6±32.2μSv (cassava). The average annual outdoor effective doses from farm soils were 0.430.32mSv for Jos and 0.210.18mSv for Abeokuta. The cancer risks due to farm soils and food ingestion were 1.42 x 10-2 and 8.57x10-3 for Jos and Abeokuta respectively. The effective doses were below the ICRP recommended limit of 1mSv and the cancer risks were slightly higher than the ICRP value of 1.0 x10-3. Cassava and yam had high radioactivity compared to other food crops. Radiological cancer risk among the population was high. The quantity of cassava and yam consumed from the areas should be reduced.